Effect of insemination site and diameter of the pre‐ovulatory follicle on the odds of pregnancy in heifers using sexed or non‐sexed semen. Issue 9 (September 2017) - Ingenhoff, L; Hall, E; Ranjbar NI, S; House, JK
Abstract : Objective: To determine if insemination site or pre‐ovulatory follicle diameter at fixed‐time artificial insemination (FTAI) affects the odds of pregnancy when heifers are inseminated with sexed semen. Methods: The study was conducted in 422 Holstein heifers enrolled into 531 inseminations. Inseminations were randomly allocated to 1 of 16 treatment combinations involving three variables: semen type (sexed vs non‐sexed), insemination site (uterine horn vs uterine body) and one of four sires. Ovaries were examined by transrectal ultrasound prior to FTAI to determine the follicle diameter and location. AI technician, times bred, age, weight and temperature–humidity index were also recorded. Pregnancy diagnosis was conducted 29 days post‐insemination. Follicle diameter and body weight were categorised according to arbitrary cut‐points. Each variable was analysed by logistic regression to determine the effect on pregnancy per AI and compare between sexed and non‐sexed inseminations. Results: Insemination site did not affect pregnancy per AI for either sexed (P = 0.528) or non‐sexed (P = 0.886) inseminations. Heifers with an 18–22 mm follicle had better odds of pregnancy than heifers that did not (odds ratio (OR) 1.45, 95% confidence interval (CI) 1.004–2.09), although no effect was detected for only sexed or only non‐sexed inseminations. Heifers weighing 310–370 kg had a higher pregnancy per AI than heifers weighing > 370 kg for non‐sexed inseminations (P = 0.004) and sexed semen from sire 4 caused lower odds of pregnancy than semen from sire 1 (OR 0.40, 95% CI 0.18–0.89). Conclusion: Insemination site did not affect pregnancy per AI, but heifers with an 18–22 mm pre‐ovulatory follicle at insemination had better odds of pregnancy for both sexed and non‐sexed inseminations.